Clinical and Neuropathological Features Associated With Loss of RAB39B. Issue 4 (17th January 2020) - Gao, Yujing; Martínez‐Cerdeño, Verónica; Hogan, Kirk J.; McLean, Catriona A.; Lockhart, Paul J.
Abstract: Background: Pathogenic variants in the small GTPase Ras Analogue in Brain 39b (RAB39B) have been linked to the development of early‐onset parkinsonism. The study was aimed at delineating the clinical and neuropathological features associated with a previously reported pathogenic variant in RAB39B (c.503C>A p.T168K) and testing for dysregulation of RAB39B in idiopathic PD. Methods: Clinical details of a male individual hemizygous for the T168K variant were collected by systematic review of medical records. Neuropathological studies of fixed brain tissue were performed and steady‐state RAB39B levels were determined by western blot analysis. Results: Neuropathological examination showed extensive dopaminergic neuron loss, widespread Lewy pathology, and iron accumulation in the substantia nigra. Additional pathology was observed in the hippocampus and thalamus. Western blot analysis demonstrated that the T168K variant results in loss of RAB39B. In individuals with idiopathic PD (n = 10, 6 male/4 female), steady‐state RAB39B was significantly reduced in the prefrontal cortex and substantia nigra. Conclusions: T168K RAB39B is unstable in vivo and associated with dopaminergic neuron loss and Lewy pathology. Dysregulation of RAB39B in the prefrontal cortex and substantia nigra of individuals with idiopathic PD potentially implicates the protein more broadly in the pathological mechanisms underlying PD and related Lewy body disorders. © 2020 International Parkinson and Movement Disorder Society